Harmony in Diversity: Islamic Perspectives on Student Perceptions and Engagement in Interfaith Dialogue on Campus - Laila Badriyah (FALASIFA : Jurnal Studi Keislaman, 2025)
This study aims to examine the perception and level of student involvement in interfaith dialogue activities in higher education as part of efforts to strengthen harmony in diversity. Universities play an important role as a strategic forum in fostering multicultural awareness and religious moderation values, especially in the midst of the complexity of society 5.0. This study uses a mixed-method approach with a quantitative descriptive design combined with qualitative analysis to produce an in-depth understanding. Data was obtained through a survey of 110 students, representing 17.2% of the total 639 students, using a proportional random sampling technique. The results showed that most students had a positive view of religious diversity (87.3%) and considered it important to maintain harmony between religious communities (79.1%). However, their level of involvement in interfaith dialogue is still low (36.4%), indicating a gap between value awareness and social practice. Although 88.2% of students did not experience discrimination based on religion, almost half (47.3%) had witnessed it happen to others, indicating that there is still potential for intolerance on campus. These findings emphasize the relevance of religious moderation theory and the idea of inclusive education which highlight the importance of the role of educational institutions in building a space for reflective, collaborative, and participatory interfaith dialogue. Thus, strengthening interreligious harmony on campus requires not only intellectual awareness, but also concrete strategies through social activities, religious digital literacy, and multicultural education based on empathy and openness.